HOOPOE: High performance and efficient anonymous handover authentication protocol for flying out of zone UAVs - Khalid, Haqi; Hashim, Shaiful Jahari; Hashim, Fazirulhisyam; Syed Ahamed, Sharifah Mumtazah; Chaudhary, Muhammad Akmal; Altarturi, Hamza H. M.; Saadoon, Muntadher (Institute of Electrical and Electronics Engineers (IEEE), 2023)
The unmanned aerial vehicles (UAVs) in military and civilian systems access sensitive data via cellular networks and are ubiquitous. Therefore, the number of handovers may increase, and the process of sharing authentication keys between drones to new drones may be vulnerable to eavesdropping due to the wireless connectivity. For example, a UAV initially served by cell A may be handed over to cell B after a certain point. Therefore, Security and privacy concerns raise if there is a change in the flight path of the UAV due to wide-area connectivity traffic management, including authentication threats as well as the leakage of identity, location, and flying routes. Also, drones are resource-constrained devices that cannot perform extensive operations, leading to the inability to resist drone capture attacks and impersonation attacks. Therefore, this paper presents a high-performance and efficient anonymous handover authentication protocol to secure the drone traveling path. The protocol utilizes the advantages of the AES-RSA algorithm to provide efficient and secure key management and a fast verification and signature generation that speeds up drone authentication. The protocol's security was proved using the formal verification ROR model and automated security verifier ProVerif tool to validate the protocol resistance against various attacks and provided forward secrecy. In addition, the performance of the proposed protocol is evaluated using the OMNeT++ simulator in terms of communication, computation cost, energy consumption, packet drop ratio, end-to-end delay, and throughput. The results showed that the protocol achieves better security, efficiency, and performance than other protocols.